The compliance revolution : how compliance needs to change to survive - Jackman, David, 1960- (Hoboken, NJ : John Wiley & Sons, Inc., 2015)
Designed to help better prepare you and your organization in implementing effective and efficient compliance procedures and practices, this book reveals the practical tools and techniques required to enhance the effectiveness of the compliance function. --
Includes index.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
Keywords: Financial services industry -- Management; Financial services industry -- Law and legislation; Financial institutions -- Management; Financial institutions -- State supervision; Financial institutions -- Law and legislation; Financial institutions -- Law and legislation; Financial institutions -- Management; Financial institutions -- State supervision; Financial services industry -- Law and legislation; Financial services industry -- Management; BUSINESS & ECONOMICS / Corporate Governance; Electronic books; Electronic books